2021
DOI: 10.1093/mnras/stab1181
|View full text |Cite
|
Sign up to set email alerts
|

The orbit and stellar masses of the archetype colliding-wind binary WR 140

Abstract: We present updated orbital elements for the Wolf–Rayet (WR) binary WR 140 (HD 193793; WC7pd  + O5.5fc). The new orbital elements were derived using previously published measurements along with 160 new radial velocity measurements across the 2016 periastron passage of WR 140. Additionally, four new measurements of the orbital astrometry were collected with the CHARA Array. With these measurements, we derive stellar masses of $M_{\rm WR} = 10.31\pm 0.45 \, \mathrm{M}_\odot$ and $M_{\rm O} = 29.27\pm 1.14 \, \mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…1, we compare the time-series observed during the two periastron passages observed by Marchenko et al (2003) and the more recent periastron passage observed by the AAVSO observers. All light curves are plotted using the binary ephemeris from Thomas et al (2021). The 2001 and 2016 periastron passages show variability in deep dips of nearly 0.1 mag in both B and V -bands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, we compare the time-series observed during the two periastron passages observed by Marchenko et al (2003) and the more recent periastron passage observed by the AAVSO observers. All light curves are plotted using the binary ephemeris from Thomas et al (2021). The 2001 and 2016 periastron passages show variability in deep dips of nearly 0.1 mag in both B and V -bands.…”
Section: Resultsmentioning
confidence: 99%
“…The most famous of these dust-producing systems is WR140 (HD 193793), a binary system containing a WC7 primary and O5.5I-type secondary. It was first discovered to have dust condensation by observation of rapid, periodic brightening in the IR by Williams et al (1978Williams et al ( , 1990Williams et al ( , 2009 and is one of two WC binaries with an established visual and double-lined spectroscopic orbit (Thomas et al 2021), but the only such system with dust emission. This system has been shown to have a 7.93 year period and a high eccentricity of 0.8993 with masses derived to better than 4% accuracy (Thomas et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WR 140 = HD 193793 is a double-lined spectroscopic binary with WC7pd and O5.5fc components (Fahed et al 2011). It is well resolved with the CHARA interferometer, which has yielded an exquisite orbit and masses for the component stars (Thomas et al 2021). The O and WR stars of WR 140 were below the resolution limit of 'Alopeke+ Gemini-N when we observed them in June 2020.…”
Section: Wr 140mentioning
confidence: 89%
“…The current state of the art in bright WR binary star resolution is the CHARA interferometer, which is resolving WR companions closer than 1 mas. This has recently resulted in well-resolved orbits for two previously known binaries: WR 137 and WR 138 (Richardson et al 2016), and in addition, solidly determined WR and O star masses for the already-known binaries WR 140 (Thomas et al 2021) and WR 133 (Richardson et al 2021). Unfortunately, CHARA is limited to stars brighter than H ∼ 8.5, and the vast majority of WR stars are fainter than this limit, so it cannot be the 'go-to' instrument in searches for new or faint companions.…”
Section: Ob and Wr Star Binariesmentioning
confidence: 94%